(untitled) (Amsterdam, 2017)
The Application of Green Solvents in Separation Processes features a logical progression of a wide range of topics and methods, beginning with an overview of green solvents, covering everything from water and organic solvents, to ionic liquids, switchable solvents, eutectic mixtures, supercritical fluids, gas-expanded solvents, and more.
Keywords: Dung môi,Solvents